Identification of Ectoparasitic Bats in Buwun Cave - Siti Rabiatul Fajri; Sucika Armiani (Jurnal Biologi Tropis, 2022)
Bats (Ordo Chiroptera) are one of the animals that have an important role in the sustainability of the ecosystem such as pollinators, seed dispersers, pest control and guano producers. In addition to their important role, bats are also animals (hosts) for several types of ectoparasites. Ectoparasites are parasitic organisms that live on the surface of the host's body. Generally, suck blood and live on the host’s hair, feathers, or skin. The research was conducted in Buwun Cave Prabu Village, Pujut District, Central Lombok Regency West Nusatenggara. Data collection on ectoparasites in bats was done manually with tweezers and a comb. Furthermore, samples of ectoparasites were identified based on sources of morphological evidence and referred to various references. The results showed that there were 3 species of bats identified, each consisting of 7 species of Eonycteris spelaea, 6 species of Rhinolopus simplex, and 3 Hipposideros diadema. Based on the results of the examination of the three bat species, there were 47 individual ectoparasites, which were identified in 3 species of ectoparasites, namely Cyclopodia horsfieldii, Amblyomma sp, and Meristapsis sp.